Engineered cement composite enhanced reinforced concrete beams using flexural response: An experimental study. (2023) - Alagunatrayan, T.; Mohanraj, P.; Manishankar, S.; Mane, Bajirao; Patil, Abhijeet; Parthiban, P.
Abstract: This review reports the outcome of an research experimental on flexural behaviour of partially strengthened reinforced concrete beams along with Engineered Cementitious Composite (ECC). 6 beams were moulded and examined in total. Three beams were tested to determine the influence of plastic hinge length, whereas two beams were examined to determine the effect of large layers of ECC in the tension zone. The remaining beam acted as control beam. Along with beam specimens, cylinders and cubes were tested to evaluate the mechanical characteristics of both ECC and concrete. All the beams are strengthened using ECC plastic hinges and layers. And they could withstand maximum load than the regulate beams. Load capacities of reinforced concrete (RC) beams strengthened with ECC plastic hinges were 2.85 – 6.34 times more than those of the corresponding control beams. Similarly, RC beams having load capacities 5.71–8.45 times with ECC layers were even better. In general, ECC application increased the ductility of Reinforced concrete beams.